Perkiraan Pasokan Nitrogen Mikrob pada Domba Ekor Tipis yang Diberi Bungkil Kedelai Terproteksi Tanin (ESTIMATION OF MICROBIAL NITROGEN SUPPLY IN THIN-TAILED SHEEP FED WITH TANNIN PROTECTED SOYBEAN MEAL) - ., Husnaeni; ., Sunarso; Nuswantara, Limbang Kustiawan (Jurnal Veteriner; Vol 16 No 2 (2015), 2015)
This research was aimed to study the effect of soybean meal protection mangrove leaf tannin onpurine derivative (PD) excretion, estimated microbial nitrogen (MN) supply, and estimated efficiency MNsuplay based on DOMR in thin-tailed sheep. A total of 16 thin-tailed sheep aged eight months withaverage body weight of 11.81±1.65 kg, and were randomly fed with complete feed with tannin-protectedsoybean meal in different levels. The research was conducted according to completely randomized designwith four treatments and four replications. T0 (soybean meal without tannin), T1 (protected soybean meal0.5% tannin), T2 (protected soybean meal 1% tannin), and T3 (protected soybean meal 1.5% tannin).Research finding indicated that organic matter consumption (OMC), organic matter digestibility (OMD),and digestible organic matter in rumen (DOMR) were not affected (P> 0.05) by the treatment, however thetreatment had significant effects (P<0.05) against PD, estimated MN supply, and estimatedMN supply based on DOMR. Purine derivative, estimated MN supply, and estimated MN supply basedDOMR markedly decreased in the treatment of soybean meal protection 1.5% tannins. It was concludedthat soybean meal protection with mangrove leaf tannins was not significant against OMC, OMD andDOMR thin-tailed sheep, but protected soybean meal with tannins 1.5% affected on decreasing purinederivative excretion, estimated MN supply and estimated MN supply based on DOMR.
Keywords: protected soybean meal, microbial nitrogen, purine derivative, tannin